Topology Optimization Study of a Refrigeration Block Manufactured with Powder Bed Fusion Selective Laser Melting - Guido Servetti; Federico Valente; Jérôme Laurent; Jitendra Singh Rathore (Journal of Manufacturing and Materials Processing)
Powder bed fusion with a selective laser melting (SLM) process is a versatile technology that allows for the manufacturing of complex geometries and lightweight structures. A prototype of a redesigned refrigeration block is made with topology optimization, thereby demonstrating the capabilities and challenges of this approach in terms of design and manufacturing. The geometry obtained was more efficient in terms of thermal performance with respect to the original design, and the simulation of the printing process indicated ways to reduce distortions. Moreover, a demonstrator was printed and measured through X-ray computed tomography (XCT) scanning, showing that the approach used was effective in terms of process parameters, technology used, and materials. In fact, it was found to have a low level of porosity, and although there were some differences in the dimensional comparison, such differences were lower in the areas where greater accuracy was required. The manufacturability was possible because of the appropriate choice of process parameters and the combination of the additive with subtractive manufacturing techniques, such as CNC milling. Overall, the methodology used proved effective for the purpose of the component in terms of thermal efficiency and weight reduction.